2020
DOI: 10.1167/iovs.61.5.3
|View full text |Cite
|
Sign up to set email alerts
|

The Appearance of the Warburg Effect in the Developing Avian Eye Characterized In Ovo: How Neurogenesis Can Remodel Neuroenergetics

Abstract: The avian eye is an established model for exploring mechanisms that coordinate morphogenesis and metabolism during embryonic development. Less is known, however, about trafficking of bioenergetic and metabolic signaling molecules that are involved in retinal neurogenesis. METHODS. Here we tested whether the known 3-day delayed neurogenesis occurring in the pigeon compared with the chick was associated with a deferred reshaping of eye metabolism in vivo. Developmental metabolic remodeling was explored using 1 H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 68 publications
(67 reference statements)
0
5
0
Order By: Relevance
“…Recently, Cherix et al (2020) demonstrated the existence of a glycolytic switch in the in ovo avian retina related to neurogenesis. This study also illustrated how neurogenesis can remodel neuroenergetics and showed the value of MRS in this instance.…”
Section: Magnetic Resonance Spectroscopy (Mrs)mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Cherix et al (2020) demonstrated the existence of a glycolytic switch in the in ovo avian retina related to neurogenesis. This study also illustrated how neurogenesis can remodel neuroenergetics and showed the value of MRS in this instance.…”
Section: Magnetic Resonance Spectroscopy (Mrs)mentioning
confidence: 99%
“…For example, Koush et al (2019) showed that j-edited fMRS at 4 T demonstrated good sensitivity and specificity for task-induced lactate modulation as well as for a smaller peak at 1.28 ppm in the motor cortex. These methodological developments could be useful for in vivo evaluation of the accumulated changes in lactate seen in other studies on neurogenesis (Prevot et al, 2018;Cherix et al, 2020).…”
Section: Magnetic Resonance Spectroscopy (Mrs)mentioning
confidence: 99%
“…In precocial Galloanserae, the need for a functional visual system at the time of hatching requires the production of RGCs at early stages, thereby de facto limiting their number. In pigeon, high level of retinoic acid and robust mitochondrial activity contribute to maintain retinal progenitors in proliferation, thereby prolonging their uncommitted status (Brodier et al, 2021; Cherix et al, 2020; Rodrigues et al, 2016). At the end of neurogenesis, the density of newborn RGCs is about three times higher in pigeon than in chicken.…”
Section: Discussionmentioning
confidence: 99%
“…Brain was extracted, DH was removed, frozen on liquid nitrogen and stored at −80 °C. Samples were then ground on mortar using liquid nitrogen, weighed and followed by a CHCl 3 /MeOH Folch-Pi extraction [ 36 , 37 ]. Samples were stirred at 4 °C in a 1:1:1 mixture of CHCl 3 :MeOH:H 2 O for 30 min after what the aqueous phase was collected and lyophilized.…”
Section: Methodsmentioning
confidence: 99%